Pengaruh Citra Perusahaan dan Kualitas Pelayanan terhadap Kepuasan Nasabah pada PT. Bank Nagari Cabang Ujung Gading - Anna Rahmadia; Afriyeni Afriyeni (JURNAL RISET MANAJEMEN (JURMA), 2024)
This research aims to determine the influence of company image on customer satisfacetion at Bank Nagari Ujung Gading Brance, the infliencer of Tangible, Empathy, Reliability, Responsiveness, Assurance, on custamer satifacetion at Bank Nagari Cabang Ujung Gading ranceh. The reselts of the analysis using SPSS version 24 show that company image has a positive and significant influence on customer satisfaction at Bank Ujung Gading Branch, and Tangible, Empathy, Reliability, Responsiveness, Assurance has a positive and significant influence on customer satisfaction at Bank Ujung Gading Branch.